THE EFFECT OF CURRENT VARIATION ON TENSILE STRENGTH IN SMAW WELDING USING SS400 STEEL - Abdullah, Salman Faruqi; Anggraini, Lydia (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2024)
Welding is one of the important processes in the manufacturing industry. One of the welding methods that is currently used is metal arc welding (SMAW) shields. In smaw welding, the electric current used has a crucial role in determining the welding characteristics, including the tensile strength of the weld joint. The aim of this research is to determine the effect of variations in current strength on the tensile strength using SS400 steel. The method used in this research is the experimental method. This research was carried out by making specimens with a V-shaped seam which were then welded using varying amperage currents of 75 A, 85 A and 95 A. The material used was SS400 steel which had a thickness of 6 mm. So, from this research, the results obtained are the highest tensile accuracy value, namely at a flow accuracy of 95 on the ker 2 sample, resulting in a total tensile accuracy value of 1180.60 Kgf. And the lowest tensile accuracy value is at 75 flow curves in the ker 1 sample, resulting in a total tensile accuracy value of 1093.88 Kgf. This is due to the fact that each variation in current accuracy greatly influences the Tensile Accuracy.